2021
DOI: 10.1002/adma.202106402
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating and Mitigating High‐Voltage Degradation Cascades in Cobalt‐Free LiNiO2 Lithium‐Ion Battery Cathodes

Abstract: LiNiO2 (LNO) is a promising cathode material for next‐generation Li‐ion batteries due to its exceptionally high capacity and cobalt‐free composition that enables more sustainable and ethical large‐scale manufacturing. However, its poor cycle life at high operating voltages over 4.1 V impedes its practical use, thus motivating efforts to elucidate and mitigate LiNiO2 degradation mechanisms at high states of charge. Here, a multiscale exploration of high‐voltage degradation cascades associated with oxygen stacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 50 publications
1
69
0
Order By: Relevance
“…When cycling under high voltage, O3-O1 phase transformation will introduce larger internal strain. [35,54] The dislocation deformation is also accompanied by decomposition, resulting in a large number of crack, as shown in Figure 3c. Grain boundary engineering can not only weaken internal strain but also eliminate lattice defects, which is of great importance for the construction of cathode materials with long-term cycling stability.…”
Section: Bulk Phase Degradationmentioning
confidence: 99%
“…When cycling under high voltage, O3-O1 phase transformation will introduce larger internal strain. [35,54] The dislocation deformation is also accompanied by decomposition, resulting in a large number of crack, as shown in Figure 3c. Grain boundary engineering can not only weaken internal strain but also eliminate lattice defects, which is of great importance for the construction of cathode materials with long-term cycling stability.…”
Section: Bulk Phase Degradationmentioning
confidence: 99%
“…Specifically, density functional theory (DFT) calculations showed that the O1 stacking sequence (AB AB AB), which appears in layered oxides at high states of charge (SOCs), is more susceptible to oxygen release than the O3 sequence (AB CA BC). 11 The kinetic origins of oxygen release have also been examined. Gas evolution mainly occurs at the surface of active materials since oxygen migration from the bulk requires overcoming high activation barriers, up to 2.4 eV for bulk LiNiO 2 .…”
Section: Atomic Levelmentioning
confidence: 99%
“…8 Upon electrochemical cycling, this atomic-level chemomechanical degradation accelerates particle-level failure mechanisms, resulting in cracking, 9 electrochemical creep, 10 or bending. 11 The origins of chemical and mechanical degradation are highly intertwined and often accelerate one another, resulting in positive feedback loops that lead to widespread loss of electrochemical activity. At larger length scales, structural characteristics and kinetic limitations within and between particles can act as additional sites for chemomechanical degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the global climate crisis, the research of new energy storage devices has been widely focused on expanding the application of renewable energy to replace fossil energy ( Tan et al, 2020a ; Wang et al, 2020a ; Gan et al, 2020 ; Cai et al, 2021a ; Liu et al, 2021a ; Cai et al, 2021b ; Deng et al, 2021 ; Zhao et al, 2021 ). In the field of new energy storage, lithium-ion batteries have been widely used because of their high energy density and wide working voltage ( Park et al, 2021 ; Xia et al, 2021 ; Feng et al, 2022 ). However, the scarcity of lithium resources increases the cost of lithium batteries, and the majority of the organic electrolyte used are poisonous or flammable, reducing the safety of lithium batteries ( Li et al, 2021a ; Du et al, 2021 ; Hou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%